Breach and compliance with community supervision in Scotland - Barry, Monica (UK Data Service, 2017)
This study of breach and compliance in Scotland uses quantitative and qualitative data to explore how offenders and professionals interpret compliance and breach; what factors relating to policy, practice and offender characteristics affect compliance and breach; and how breach policy and practice can be enhanced so as to encourage the cessation of offending. A literature review, the collection of aggregate data nationally and 375 interviews with professionals and offenders in 3 case study areas are the 3 methods to be used. The study seeks to impact politically (boosting confidence in criminal justice social work amongst the judiciary, offenders and the wider public), economically (ensuring that social work engagement with offenders works to secure their cooperation and reintegration), and operationally (offering new ways for supervising social workers to engage meaningfully with offenders subject to community-based disposals and post-custodial orders). Over 40 per cent of people serving community punishments are subject to breach (not complying with a disposal because of further offending or failing to keep to conditions), yet the processes of compliance and breach are little understood or researched.